Analyzing the Distribution of Family Income in Erbil’s Urban Population using Pareto Distribution and its Properties - Mardin Samir Ali (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
In the real life there are many phenomena that have Pareto distribution’s properties. One of the useful applications of this distribution is family income. This study aims to understand Pareto distribution, its properties, and fitting the family income to Pareto distribution. The Data were collected through a questionnaire distributed to 290 families; the sample covered just urban population in Erbil city. The data analyses of the family income done through applying EasyFit v.5.4 mainly, Statgraphics v.15, and MS Excel 2016 programs. The Pareto distribution with two parameters (α=0.646 and β=5) was discovered to be the best fit for this type of data. It is suggested that local authorities adopt the proposed distribution to reap the benefits of applying pareto distribution to future KRG plans aimed at increasing the income of Kurdish families